2018
DOI: 10.1371/journal.pone.0195582
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity practices on Australian commercial layer and meat chicken farms: Performance and perceptions of farmers

Abstract: This paper describes the level of adoption of biosecurity practices performed on Australian commercial chicken meat and layer farms and farmer-perceived importance of these practices. On-farm interviews were conducted on 25 free range layer farms, nine cage layer farms, nine barn layer farms, six free range meat chicken farms and 15 barn meat chicken farms in the Sydney basin bioregion and South East Queensland. There was a high level of treatment of drinking water across all farm types; town water was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 20 publications
1
40
1
Order By: Relevance
“…These motile organisms might be vectors for C. hepaticus dissemination. A recent study that investigated biosecurity practices on Australian commercial layer farms showed that wild birds were commonly reported to be present in free-range farms (73%) and it was noted that they are potential sources of diseases that can be transmitted to laying hens (31). Flies have previously been implicated in the transmission of other Campylobacter species to chickens (32).…”
Section: Discussionmentioning
confidence: 99%
“…These motile organisms might be vectors for C. hepaticus dissemination. A recent study that investigated biosecurity practices on Australian commercial layer farms showed that wild birds were commonly reported to be present in free-range farms (73%) and it was noted that they are potential sources of diseases that can be transmitted to laying hens (31). Flies have previously been implicated in the transmission of other Campylobacter species to chickens (32).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to poultry enterprises this refers to practices, such as the use of foot baths, treatment of water, disinfection of equipment between sheds, and vermin control ( 34 ). It was found during on-farm surveys that non-free-range meat chicken farms were usually older farms with relatively poorer biosecurity compared to free-range meat chicken farms ( 12 ). This relative lack in biosecurity contributed to the highest median probability of indirect exposure occurring in non-free-range meat chicken farms compared to the rest of the farm types.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the input values used in this model were parameterized using data collected from a survey on commercial chicken farms in Australia ( 11 , 12 ). The survey defined commercial layer farms as those with more than 1,000 birds and commercial meat chicken farms as those with more than 25,000 birds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…border collie) have been used to scare off wild birds (Castelli & Sleggs, 2000;Holevinski, Curtis, & Malecki, 2007). In Australia, some free-range poultry farms use trained Maremma breed dogs to limit interaction between wild fauna and poultry (AGDAFF, 2009;Gibbs, ;Scott, Singh, et al, 2018b). Laser equipment is used for several years to scare off wild birds, in particular geese (Blackwell, Bernhardt, & Dolbeer, 2002;Gorenzel, Blackwell, Simmons, Salmon, & Dolbeer, 2002;Werner & Clark, 2006).…”
Section: Known Carriers Of Ai Viruses Visit the Outdoor Facility Regumentioning
confidence: 99%